USING FAIRY TALE ILLUSTRATED VERSION TO IMPROVE STUDENTS READING COMPREHENSION - Hairunnisyah, Nurindah; Darmawan; Wahyudin (e-Journal of ELTS (English Language Teaching Society), 2024)
The research aims to find out whether using Fairy Tale Illustrated Version can improve students reading comprehension of the tenth grade students of MAN 2 Kota Palu. The researcher applied quasi-experimental research design. The samples of this research were 64 students, which were divided into 33 students of class X MIPA 2 as the experimental group and 31 students of class X MIPA 1 as the control group. The samples were selected use purposive sampling technique. The data were collected through the reading test that consisted of pre-test and post-test. The result of the pre-test shows that the mean score of the experimental group is 45.33 while the mean score of the control group is 49.68. This demonstrated that the pre-test mean score of the experimental group were lower compared to the control group. After conducting the treatment, the result of the post-test shows that the mean score of the experimental group is 71.76 while the mean score of the control group is 59.87 It indicates that the experimental group has shown improvement in their reading comprehension compared to the control group. By applying 62 degree of freedom (df) and 0.05 level of significance, it can be seen that the t-counted (9.20) is higher than the ttable (1.999). It means that the hypothesis was accepted or Using Fairy Tale Illustrated Version can improve students’ reading comprehension of The Tenth Grade of MAN 2 Kota Palu.